Erin completed the problem correctly. She accurately expanded the binomials and combined like terms. Her calculation shows:
- \( (2x)(x) = 2x^2 \)
- \( (2x)(12) = 24x \)
- \( (-5)(x) = -5x \)
- \( (-5)(12) = -60 \)
When combining the like terms \( 24x \) and \( -5x \), she correctly calculated \( 24x - 5x = 19x \). Thus, the final result is \( 2x^2 + 19x - 60 \).
On the other hand, Joey made a mistake in combining the terms after expansion. He started correctly with:
- \( (2x)(x) = 2x^2 \)
- \( (2x)(12) = 24x \)
- \( (-5)(x) = -5x \)
- \( (-5)(12) = -60 \)
However, when he combined the like terms \( 24x \) and \( -5x \), he incorrectly computed them as \( 21x \) instead of \( 19x \). Therefore, his final result of \( 21x - 60 \) is incorrect because he failed to correctly add the coefficients of the \( x \) terms. As a result, he had the wrong coefficient for the \( x \) term in his final answer.